Overview on actual status of world’s and Vietnam’s marine biodiversity - Thanh, Dang Ngoc (Academia Journal of Biology, 2012)
﻿Based on recently published IUCN Red List 2008 and other current documents, an overview on the actual status of the marine biodiversity in the world and in Vietnam particularly is given in the paper. By continents, Asia is in first rank, having the greatest number of threatened wild animals (6,755 species), of which 663 inCritically Endangered (CR). America is in second rank (5,502 species), but with a high number of wild animals categorized as Extinct (EW, EX). Africa and Europe are continents having relatively low number of threatened wild animals, rest reactively 4,504 and 2,800 species, although number of animals in CriticallyEndangered category (552 species) and Extinct Category (241 species) are high in Africa. During a period, notso long, from 1990-2005. A remarkable increasing trend of threatened situation of the marine species diversityin the world as well as in Vietnam has been recorded. It was expressed not only on the increasing number ofthreatened species, but also on the threatened categories in different groups marine as well as fresh water animals. For first time, in the Vietnam Red List 2007, has recorded marine and freshwater animals categorized as extinct in the wild (EW). At the same time, a great number of marine animals (fishes, turtles,dugong and invertebrates) must be considered as in CR, EN categories. Hence, some actual problems of marine biodiversity conservation are given and discussed by the author in the paper.In comparison with land animals, in the past time, marine animals ware fewer to be evaluated threatened status. So that, justly to 2008 year, among 41. 500 assessed animals, only 1500 marine species has been evaluated and listed in IUCN Red List, including marine fishes, mammals, birds, corals turtles